Fertilizer Information System for Banana Plantation - Yu Shin Shuen; Nureize Arbaiy; Yusmadi Yah Jusoh (JOIV : International Journal on Informatics Visualization, 2017)
A banana is a nutritious fruit which contains good vitamins and nutrient for body. Banana tree requires suitable mean temperature and mean rainfall to grow up. Additionally, healthy soil improves crops growth due to sufficient nutrients. Farmers use fertilizer to improve soil nutrient and increase yield productions. Thus, a proper field management and fertilization is important to ensure banana plants to produce high quality of yield. Improper manage fertilizer will cause impact on the environment and affect the banana plantation. Therefore, fertilizer information system for banana plantation is developed to support farmers to manage information for banana farm in an effective way. Prototype model is employed to assist development of the system. PHP programming language is used to develop this system and MySQL as a system database. This system contains five modules which are registration and login module, manage banana plantation information module, fertilizer formulation management module, fertilizer information management module and report module. It is expected that the system will help farmers to manage and monitor the fertilizing task in the farm efficiently.